Fickle Fossils. Economic Growth, Coal and the European Oil Invasion, 1900-2015 - Miriam Fritzsche; Nikolaus Wolf (Center for Economic Studies and ifo Institute (CESifo), 2023)
Fossil fuels have shaped the European economy since the industrial revolution. We use new long-run panel data to analyse the effect of both, coal and oil on economic growth between 1900 and 2015, exploiting variation at the level of European NUTS2 and NUTS3 regions. We show that the reversal of fortune of coal regions resulted from the second energy transition. Specifically, an "oil invasion" in the early 1960s turned regional coal abundance from a blessing into a curse. Human capital accumulation contributed to this reversal of fortune and fully explains the negative effects until today. Moreover, we find substantial heterogeneity between former coal regions that is in line with Glaeser's "reinvention hypothesis": regions with a higher skill-level adjusted much better to the decline of coal. In particular, we show that coal regions with a higher urban density before 1800 were much more resilient than others.
Keywords: O13; O44; Q32; N14; R10; I25; 330; coal; oil invasion; second energy transition; education; reinvention; growth